2015
DOI: 10.2147/copd.s87259
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of body mass index among subjects with COPD in the Middle East and North Africa region: data from the BREATHE study

Abstract: BackgroundData describing the potential relationship between chronic obstructive pulmonary disease (COPD) and body mass index (BMI) are limited within the Middle East and North Africa (MENA) region.ObjectiveTo evaluate the distribution of BMI among subjects with COPD in the general population of the MENA region.MethodsThis study was a subanalysis of the BREATHE study, a cross-sectional survey of COPD conducted in the general population of ten countries in the MENA region and Pakistan. The study population cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 27 publications
1
13
0
2
Order By: Relevance
“…This study examined the association of weight and health outcomes, specifically among patients with mild to moderate COPD. The findings on comorbid disorders complement to results of previous observational studies that were conducted in the general COPD population, regarding diabetes, 2 4 , 6 9 hypertension, 2 , 6 9 osteoarthritis, 9 and osteoporosis. 9 Regarding cardiovascular diseases, we found positive associations for obesity and heart failure, but not for coronary heart disease and stroke.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This study examined the association of weight and health outcomes, specifically among patients with mild to moderate COPD. The findings on comorbid disorders complement to results of previous observational studies that were conducted in the general COPD population, regarding diabetes, 2 4 , 6 9 hypertension, 2 , 6 9 osteoarthritis, 9 and osteoporosis. 9 Regarding cardiovascular diseases, we found positive associations for obesity and heart failure, but not for coronary heart disease and stroke.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies that investigated the implications of overweight and obesity on health outcomes were conducted only in the overall COPD population, including patients with severe COPD. 3 , 4 , 8 10 However, in patients with COPD, excess weight is mainly present among those with milder stages of COPD. 15 These patients are generally treated in primary healthcare, and it therefore seems relevant to study the association of weight and health outcomes specifically in patients with mild to moderate COPD.…”
Section: Introductionmentioning
confidence: 99%
“…The proportions of obese patients were 29.6% according to the studies on the distribution of BMI among patients with COPD in both Spain 44 as well as the Middle East and North Africa. 45 The study by Rodríguez et al showed that the proportion of the obese was 43% among the selected patients with COPD. 46 In addition, when evaluating the clinical parameters associated with BMI, such as health-related quality of life, dyspnea score, and respiratory functions, Asia-Pacific classifications can be more appropriate than WHO classifications in Asian patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, esta observación es contraria a lo reportado por Lambert, et al, quienes mostraron que en [130] conjunto los pacientes con mayor IMC (obesos) presentaron con mayor frecuencia clase GOLD D que los pacientes con peso normal o sobrepeso (15) . Por otro lado, McCormack, et al, observaron en una muestra de 84 pacientes que el IMC (peso normal y obesidad) no se asoció a la categoría GOLD (17) ; esta independencia la replicaron también Koniski, et al, con una muestra de 996 pacientes, donde encontraron que el IMC no se relacionó significativamente con la clase GOLD (18) .…”
Section: Discussionunclassified
“…Los estudios precedentes mostraron una asociación consistente entre la obesidad y las gradaciones I a IV de GOLD (valor aislado del VEF1) con las comparaciones con estadística paramétrica (9)(10)(11)(12)(13)(14) . Sin embargo, los hallazgos de la asociación son divergentes o difíciles de interpretar en aquellos análisis realizados con una aproximación no paramétrica (15)(16)(17)(18) .…”
Section: Introductionunclassified